Topographische Grenzgänge in die Unterwelt: Sterben als Suche in David Grossmanns Aus der Zeit fallen - Harmening, Anda-Lisa Martha Josephine Anna (Störungen des 'Selbst' – Trauma-Erfahrungen und Möglichkeiten ihrer künstlerischen Konfiguration)

(Text)Körper und Macht – Politische Interventionen in Juli Zehs Corpus Delicti - Harmening, Anda-Lisa Martha Josephine Anna (Politische Interventionen und Spielräume in der Gegenwartsliteratur von Autorinnen)

Intersections of Gender and Myth in canadian culture and Media

Schmierstoffentwicklung für E-Antriebe: Der Teufel steckt im Detail - Magyar, Balázs; Freise, Rainer (Experten-Forum Powertrain: Reibung in Antrieb und Fahrzeug 2019)
In diesem Beitrag werden zuerst die Hauptanforderungen für Schmierstoffe für die E-Mobilität dargestellt. Anschließend wird erklärt, welche technische Herausforderungen aus den sehr unterschiedlichen Anforderungen der einzelnen Komponenten resultieren. Danach wird der Einfluss der Grundölsorte, der Viskosität und der Additivierung diskutiert. Zum Schluss werden die typischen Unverträglichkeiten der eingesetzten Materialien und die damit verbundenen Schadensarten bzw. die Tests zur frühzeitigen Aufklärung, vorgestellt.

Friction Energy-Based Wear Simulation for Radial Shaft Sealing Ring - Foko Foko, Flavien; Heimes, Julia; Magyar, Balázs; Sauer, Bernd (Lubricants)
Radial shaft sealing rings (RSSR) are important machine elements used in rotating and oil lubricated systems. Their main task is to prevent oil from exiting the system and dirt particles from entering the system. When this function is not fulfilled, a leakage can occur and cause excessive damage after certain operating times, such as gear failure due to insufficient lubrication. This is the reason for the high level of current research interest in seals. The sealing function of RSSR occurs in the contact area between the sealing lip and the shaft. The contact takes place over a very small contact width of approximately 1 μm. These extremely small dimensions and the complex relationships between the functional influencing variables on the radial shaft sealing system make it difficult to simulate wear on the sealing ring. The energetic consideration of the wear process offers the possibility of quantifying influencing variables more easily by their energetic contribution, which can be determined experimentally. Based on experimentally measured total friction moments, and with the help of a semi-analytical (SA) solid contact model based on the half-space theory, this paper presents a modelling approach for the calculation of wear at the sealing ring. The model presented in this work differs from the existing models in two ways. The first particularity is the coupling of SA method with finite element method (FEM) for the resolution of the contact between the sealing lip and the shaft, allowing a fine discretization of the contact zone (by SA method) and the consideration of the structural behavior (by FE method). The SA method compared to the commonly used FEM presents a great saving in computation time. The second particularity is the use of the real data obtained during the wear tests. Most existing simulation models are based purely on contact pressure. This means that through the contact pressure obtained by simulation and a given sliding distance value, a friction energy will be estimated which will be used in a next step using a wear model such as Archad’s to calculate the wear rate. In this publication the value of friction energy was obtained directly on an experimental basis and a more appropriate wear law, such as Fleischer’s, taking into account the friction conditions, was used to estimate the wear rate.

Thermoelastohydrodynamic Lubrication Simulation of Radial Shaft Sealing Rings - Thielen, Stefan; Magyar, Balázs; Sauer, Bernd (Journal of Tribology)
Regarding the increasing demand in seal lifetime and energy efficiency, a detailed microscopic simulation is necessary—as an addition to experimental investigations—to better understand and improve radial shaft seals. For this purpose, typically thermoelastohydrodynamic lubrication (TEHL) simulations are used. The published models range from rather simple elastohydrodynamic lubrication (EHL) models to very sophisticated TEHL models. Only very few models take into account the roughness or microstructure of both contact surfaces, though, since this would require the consideration of transient effects. In this article, a transient TEHL model for the contact of radial shaft seals is presented. Studies of the sealing contact are conducted, and the possibility of investigating shaft microstructuring is shown.

Training athletes with an external attentional focus enhances athletic performance during countermovement jump - Letafatkar, Amir; Rabiei, Pouya; Ghanati, Hadi Abbaszadeh; Khosrokiani, Zohre; Ghahremani, Naji; Gokeler, Alli (Sport Sciences for Health)
Keywords: Orthopedics and Sports Medicine

Restricting ankle dorsiflexion does not mitigate the benefits of external focus of attention on landing biomechanics in healthy females - Haines, Mackenzie; Murray, Amanda M.; Glaviano, Neal R.; Gokeler, Alli; Norte, Grant E. (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Erfassung von Einstellungen zu Inklusion mit SACIE, EFI-L und KIESEL - Gorges, Julia; Grumbach, Jasmin; Micheel, Sabrina A.; Neumann, Phillip (Diagnostica)
Zusammenfassung. Positive Einstellungen zu Inklusion gelten als zentraler Erfolgsfaktor für die Entwicklung eines inklusiven Schulsystems. Die vorliegende Studie prüft die Validität dreier gängiger deutschsprachiger Messinstrumente zur Erfassung von Einstellungen zu Inklusion in einer unabhängigen Stichprobe: SACIE, EFI-L und KIESEL. Zur Validierung herangezogene externe Konstrukte sind Selbstwirksamkeit und die Big Five Persönlichkeitsfaktoren. Die Ergebnisse einer Befragung von 556 Lehrkräften und Lehramtsstudierenden (Alter: M‍( SD) = 26.48 (12.67); 70 % weiblich) mit Blick auf die Inklusion von Kindern mit Förderschwerpunkt Lernen (SPF-L) zeigen eine weitgehend gute Replizierbarkeit der Faktorstrukturen der Instrumente. Die Faktorkorrelationen über die Instrumente hinweg lagen zwischen |.61| und |.96| (nur Attitude Subskala des SACIE). Alle Subskalen zeigen vergleichbare Zusammenhänge mit Selbstwirksamkeit und den Big Five Persönlichkeitsfaktoren. Zwar weisen Unterschiede in den Effektstärken darauf hin, dass die Instrumente je spezifische Aspekte von Inklusion betonen, insgesamt rechtfertigen die Ergebnisse jedoch die Annahme, dass das zugrundeliegende Konzept von Einstellungen bezüglich Inklusion weitgehend überlappt.
Keywords: Inklusion; Einstellungen; Inclusion; BiFoKi

Diagnostik in inklusiven Schulen – zwischen Stigmatisierung, Etikettierungs-Ressourcen-Dilemma und förderorientierter Handlungsplanung - Neumann, Phillip; Lütje-Klose, Birgit (Schüler*innen mit sonderpädagogischem Förderbedarf in Schulleistungserhebungen)
In diesem Beitrag wird die Frage diskutiert, ob und welche diagnostischen Konzepte in einem inklusiven Schulsystem umgesetzt werden können und sollten und welche Konsequenzen sich daraus für die Erforschung inklusiver Modelle und Praktiken ergeben. Einem historischen Abriss über die Entwicklung unterschiedlicher diagnostischer Perspektiven hinsichtlich der Feststellung sonderpädagogischen Unterstützungsbedarfs folgt eine kritische Diskussion unter den Stichworten Statusdiagnostik versus Prozessdiagnostik. Vor diesem Hintergrund werden Einsatzbereiche, Vorzüge und Nachteile von formellen und informellen Verfahren aus inklusions- und sonderpädagogischer Perspektive betrachtet. Anschließend erfolgt eine Systematisierung unterschiedlicher Zielsetzungen (sonder-)pädagogischer Diagnostik unter besonderer Berücksichtigung ihrer Einsatzbereiche und Umsetzungsformen. Deren möglicher Informationsgehalt sowie die jeweiligen Konsequenzen für empirische Studien in der Bildungsforschung werden zum Abschluss diskutiert.
Keywords: Inklusion; Diagnostik; Kategorisierung; De-Kategorisierung

Kooperation als Schlüssel - Das "Bielefelder Fortbildungskonzept zur Kooperation an inklusiven Schulen" (BiFoKi) - Wild, Elke; Lütje-Klose, Birgit; Gorges, Julia; Neumann, Phillip; Grüter, Sandra; Weber, Antonia; Goldan, Janka (SEMINAR - Lehrerbildung und Schule)
Keywords: BiFoKi; Inklusion; Fortbildung; Schulentwicklung; Kooperation; Eltern; Schule-Eltern-Kooperation; Bildungspartnerschaften

Co-movement of Price and Intrinsic Value-Does Accounting Information Matter? - Mehring, Oliver; Olsson, Per; Sievers, Soenke; Sofilkanitsch, Christian

Co-movement of Price and Intrinsic Value-Does Accounting Information Matter? - Mehring, Oliver; Olsson, Per; Sievers, Sönke; Sofilkanitsch, Christian

Does Learning About Low GAAP Reporting Quality Change Investors’ Perceptions of Aggressive Non-GAAP Reporting Choices? - Mehring, Oliver; Müller, Jens; Sievers, Sönke; Sofilkanitsch, Christian

Online Appendix to: Co-movement of Price and Intrinsic Value-Does Accounting Information Matter? - Mehring, Oliver; Olsson, Per; Sievers, Sönke; Sofilkanitsch, Christian

Paying for performance in private equity: Evidence from venture capital partnerships - Hüther, Niklas; Robinson, David T; Sievers, Sönke; Hartmann-Wendels, Thomas (Management Science)

What are the effects of strategy consultants, financial, and legal M&A advisors on M&A success? - Schmitz, Alexander; Sievers, Sönke

Kinetic studies of cathode degradation on PEM fuel cell short stack level undergoing freeze startups with different states of residual water and current draws - Liphardt, L.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Herausforderungen inklusiver Bildung in Kita-Teams – Konzipierung eines individualisierten Curriculums für Weiterbildung und Prozessbegleitung - Albers, Timm; Weltzien, Dörte; Ali-Tani, Caroline; Döther, Sabrina; Söhnen, Sarah Aileen; Verhoeven, Nadja (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

Transitionsprozess im Kontext von Inklusion: Theoretische und empirische Zugänge zur Gestaltung des Übergangs vom Elementar- in den Primarbereich - Albers, Timm; Lichtblau, Michael (Kooperation von KiTa und Grundschule ; Band 2: Digitalisierung, Inklusion und Mehrsprachigkeit)

Lie groupoids of mappings taking values in a Lie groupoid - Amiri, Habib; Glöckner, Helge; Schmeding, Alexander (Archivum Mathematicum)
Keywords: 22A22; 22E65; 22E67; 46T10; 47H30; 58D15; 58H05

Products of regular locally compact spaces are k_R-spaces - Glöckner, Helge; Masbough, Niku (Topology Proceedings)
Keywords: 54B10; 54D45; 54D50

Smoothing operators for vector-valued functions and extension operators - Glöckner, Helge (arXiv:2006.00254)
For suitable finite-dimensional smooth manifolds M (possibly with various kinds of boundary or corners), locally convex topological vector spaces F and non-negative integers k, we construct continuous linear operators S_n from the space of F-valued k times continuously differentiable functions on M to the corresponding space of smooth functions such that S_n(f) converges to f in C^k(M,F) as n tends to infinity, uniformly for f in compact subsets of C^k(M,F). We also study the existence of continuous linear right inverses for restriction maps from C^k(M,F) to C^k(L,F) if L is a closed subset of M, endowed with a C^k-manifold structure turning the inclusion map from L to M into a C^k-map. Moreover, we construct continuous linear right inverses for restriction operators between spaces of sections in vector bundles in many situations, and smooth local right inverses for restriction operators between manifolds of mappings. We also obtain smoothing results for sections in fibre bundles.

Lie groups of real analytic diffeomorphisms are L^1-regular - Glöckner, Helge (arXiv:2007.15611)
Let $M$ be a compact, real analytic manifold and $G$ be the Lie group of all real-analytic diffeomorphisms of $M$, which is modelled on the (DFS)-space ${\mathfrak g}$ of real-analytic vector fields on $M$. We study flows of time-dependent real-analytic vector fields on $M$ which are integrable functions in time, and their dependence on the time-dependent vector field. Notably, we show that the Lie group $G$ is $L^1$-regular in the sense that each $[\gamma]$ in $L^1([0,1],{\mathfrak g})$ has an evolution which is an absolutely continuous $G$-valued function on $[0,1]$ and smooth in $[\gamma]$. As tools for the proof, we develop several new results concerning $L^p$-regularity of infinite-dimensional Lie groups, for $1\leq p\leq \infty$, which will be useful also for the discussion of other classes of groups. Moreover, we obtain new results concerning the continuity and complex analyticity of non-linear mappings on open subsets of locally convex direct limits.

Literatur im Studium Deutsch als Fremdsprache und in der internationalen Germanistik: Sprachbildung und Förderung interkultureller Kompetenzen durch literarische Texte - Zierau, Cornelia (Germanistik im Kontext des LMD-Systems. Didaktische und curriculare Herausforderung einer regionalen Hochschulpolitik für das Deutsch-Studium in Westafrika)

Sprachsensibler Literaturunterricht mit „Tschick“. Sprachliches und literar-ästhetisches Lernen in einem integrativen Deutschunterricht? - Zierau, Cornelia; Kofer, Martina (Sprache als Herausforderung – Literatur als Ziel. Kinder- und jugendliterarische Texte und Medien als Ressource für sprachsensibles Lernen Teil 2)

Übergänge gestalten – eine Herausforderung - Zierau, Cornelia; Jung, Ulla (DaZ Sekundarstufe. Konzepte und Materialien: Übergänge gestalten – neu Zugewanderte unterrichten, Heft 1/2020)

„Ich verkaufte ihm meinen Fastentag für 25 Kuruş und mit diesem Geld ging ich ins Kino.“ Mehrsprachigkeit und Übersetzung ,türkischer’ Kultur in Emine Sevgi Özdamars Roman „Das Leben ist eine Karawanserei“ - Zierau, Cornelia (Peter Weiss Jahrbuch)

Weltenübergänge in Fargo - Diester, Michel (ffk Journal, Nr. 5)

Co-movement of Price and Intrinsic Value-Does Accounting Information Matter? - Mehring, Oliver; Olsson, Per; Sievers, Soenke; Sofilkanitsch , Christian; Uhde, André; Eber, Michael

A Kind of Sovereignty? Legitimising Freedom of Contract in the 18th Century - Süßmann, Johannes (Languages of Reform in the Eighteenth Century. When Europe Lost Its Fear of Change)

Albrecht und Isabella in Brüssel. Eine Spurensuche - Süßmann, Johannes (Erinnerungsorte in Belgien. Instrumente lokaler, regionaler und nationaler Sinnstiftung)

Barock im Norden. Kommunikationspraxis und Kulturtransfer - Ehland, Christoph; Laak, Lothar van; Münzmay, Andreas; Schmitz, Sabine; Süßmann, Johannes (Peter Paul Rubens und der Barock im Norden. Katalog zur Ausstellung im Erzbischöflichen Diözesanmuseum Paderborn)

Gehl, Katerina/Roth, Klaus/Spiritova, Marketa (Hg.): Eigenbilder – Fremdbilder – Identitäten. Wahrnehmungen im östlichen Europa im Wandel (Ethnographische Perspektiven auf das östliche Europa, 5), Bielefeld 2020 - Hansen, Christin (Jahrbuch kulturelle Kontexte des Östlichen Europa)

Micro-Inverters: An Update of Comparison of Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EUPVSEC 2020)
Efficiencies and energy yields of microinverters available on the market during 2014‒2020 have been measured, compared, and ranked. Conversion efficiencies as a function of load have been measured indoors with high accuracy and ranked according to Euro- and CEC weightings. Energy yields have been measured outdoors via identical and calibrated crystalline silicon PV modules of 215 Wp each. Inverters with two inputs have been fed by two of those modules. DC input, AC power output and energy yield of each micro-inverter have been recorded by individual calibrated electricity meters. Apparently, some inverters have been optimized for high irradiance levels and ranked better at the CEC efficiency ranking, others performed very well also at low irradiance levels, thus ranking higher at in the EU efficiency ranking. Efficiency ranks are slightly deviating from rankings by energy yield measurements. At one inverter, a slow MPPT algorithm that barely could follow quickly changing irradiance levels is most probably responsible for this effect. Another inverter switched off for a while after operation at high power, another one failed permanently. Apparently, some inverters are been optimized to show excellent datasheet ratings for EU- or CEC- efficiency. On the other hand, two inverters (each featuring two inputs) did not show an outstanding performance at the EU- and CEC-ratings but achieved leading ranks for AC energy yields. For the customer, AC yield is a major performance indicator of a microinverter and should be included in the datasheet.

Einfluss der Betriebstemperatur auf den Wirkungsgrad von Modul-Wechselrichtern für PV-Netzeinspeisungen - Krauter, Stefan; Bendfeld, Jörg (Tagungsband des 35. Symposiums für Photovoltaische Solarenergie, Kloster Banz, Bad Staffelstein (Deutschland))

Triggering Demand‒Side‒Management: Correlation of electricity prices, share of renewables, CO2‒contents, and grid‒frequency in the German electricity grid. - Krauter, Stefan; Zhang, L. (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020.)
To provide a simple instrument to operate residential Load-Shifting or Demand-Side-Management systems, the measurement of the actual grid frequency seems to be an appropriate method. Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation. While the specific CO2- emission is decreasing then ‒ due to the increased share of Renewables, the grid frequency is increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side management indicator to lower specific CO2‒emssions and costs (if a dynamic consumption tariff is available). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and a the correlation between grid frequency, power surplus, share of renewables vs. CO2-contents and price at the European energy exchange (EEX) have been calculated. The results show: Correlation between frequency and share of renewables is quite low (r = 0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. There is a good anti-correlation (r = - 0.687) between the EEX‒prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r =0.665), within the one year (2018) that correlation almost doesn’t exist, possibly due to the inflexibility of the bulky lignite power plants that even operate at negative prices.
Keywords: Keywords: Load-Shifting; Demand-Side-Management; DSM; grid frequency; EEX; electricity trading prices; renewable share; flexibility; emissions; CO2

Reduction of required storage capacities for a 100% renewable energy supply in Germany, if new PV systems are installed with east-west tracking systems at increased elevation angles - Krauter, Stefan; Rustemovic, D.; Khatibi, Arash (Proceedings of the 37th European Photovoltaic Solar Energy Conference, 07 - 11 September 2020)
Due to the strong reduction of PV prices, storage plays a dominating role in overall system costs. A steeper elevation angle would result in a more balanced seasonal PV yield, at the cost of PV yield reductions during summer, but allowing reduced storage capacities. Additionally, the effect of a single-axis tracking system has been investigated, generating more electricity during the morning and evening hours, thus reducing daily storage requirements. The necessary PV size and storage capacities required for the German energy supply (1,500 TWh after electrification of all sectors) via 100% renewable energies and a 50% solar share have been calculated via the HOMER Pro software, considering the bridging of periods of "dark lulls“ in winter, using costs of 2030 (Table 1). Results: The increase of module elevation angles above the typical 30° leads to a reduction of investment and supply costs. The optimum is reached at a cost reduction of -1.5% for an elevation angle at the latitude of the installation site. An explanation is that high elevation angles are favorable for clear winter days, but not at all for the critical days with diffuse irradiance only, so the battery capacity must be increased. For the same reason, tracking systems do not offer any cost advantage (at least for the ones without an option for horizontal positioning during diffuse days).
Keywords: Energy Storage; PV system integration; Large Grid-connected PV systems; Simulation; Energy Supply Options

Elevated Temperatures Affecting Efficiency, Overall Performance and Energy Yield of PV Microinverters - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the EU PVSEC 2020)
During comparative measurements of different PV microinverters, two yield issues came up that could not be explored via conventional efficiency measurements, but do have a significant impact on electrical energy yield: First category of issues are either sluggish or nervously acting maximum–power–point–tracking devices, which lead to reduced energy yields. The other category of issues is thermal: As a first explanation for observed reduced energy yields, it has been assumed that the conversion efficiency degrades at higher operating temperatures. This matter has been investigated in this article: A change in conversion efficiency could not be observed for elevated operation temperatures up to 50°C, despite high-precision and repeated measurements. But it was found that some inverters temporarily interrupted (or entirely stopped) operation after long periods of running at high temperatures. Also, a reduction in potential maximum power output has been detected for those inverters. Summarizing: With a high degree of certainty it can be stated that those reported yield losses have been caused by the temporary shutdowns and power limitations of the inverters.
Keywords: AC-modules; Microinverter; Power Conditioning; Thermal Performance; Ventilation; Stability; Efficiency; Yield

Correlation of grid-frequency, electricity prices, share of Renewables and CO2-contents of German electricity grid to enable inexpensive triggering of Demand-Side-Management - Krauter, Stefan; Zhang, L. (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) 2020)
Due to the present inflexibility and the lack of sufficient throttling capabilities of lignite and nuclear power plants, a surplus of electricity generation occurs during periods of high wind and solar power generation in the German electricity grid. While the specific CO2-emission is decreasing then - due to the increased share of Renewables, the grid frequency should be increasing (to a certain limit). Using the grid frequency as an indicator to switch-on and -off certain loads (loads that do not require power permanently (e.g. dishwashers, washing machines, dryers, fridges and freezers, heaters) could provide a simple, inexpensive demand-side-management indicator to lower specific CO2-emissions and costs (if a dynamic consumption tariff is applied). To check the truthfulness of that hypothesis, the grid and frequency data of the German grid of the year 2018 have been collected and the correlations between grid frequency, share of renewables, CO2-contents, and actual price at the European energy exchange (EEX) have been calculated. The results show: Correlation between grid frequency and the share of renewables is quite low (r=0.155) due to the fact that primary grid control quickly compensates deviations from the 50 Hz nominal frequency. As expected, there is a good anti-correlation (r=-0.687) between the EEX-prices and the share of renewables in the grid. Over the years, correlation between electricity trading prices (EEX) and CO2 emissions is quite good (r=0.665), within the one year (2018) that correlation almost doesn't exist, possibly due to the inflexibility of the bulky lignite baseload power plants that even operate at negative prices.
Keywords: CO2; EEX; Grid frequency; DSM; electricity price; Renewable share

Comparison of Microinverters: Update on Rankings of Conversion Efficiencies and Energy Yields - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 47th IEEE Photovoltaic Specialists Conference (PVSC 47) JUNE 15 - AUGUST 21, 2020 VIRTUAL MEETING)
To compare efficiency and yield of many micro-inverters available on the world market in 2014-2020, an in- and outdoor test laboratory at the University of Paderborn has been set up. The inverters have been fed by identical and calibrated crystalline silicon PV modules of 215 Wp. To monitor accurately DC input, AC power output and energy yield, each of the micro-inverters has been equipped with a calibrated electricity meter. For micro-inverters requiring control units for grid-feeding that has been acquired also. The comparison covers efficiency-load characteristics as well as electrical energy yields. Purchase costs vary considerably between the models in comparison, sometimes inverter costs are higher than module costs, particularly if an additional grid-connection or interface device is needed for operation. The weighted conversion efficiency according to EU and CEC standards has been measured and calculated. While some inverters have been optimized for high irradiance levels, they ranked better at the CEC efficiency, others performed very well also for low irradiance levels, thus ranking higher at in the EU-efficiency tables. These results are deviating from the actual energy yield measurements, which show a slightly different ranking. At one inverter, an accurate, but very slow MPPT algorithm that barely could follow quickly changing irradiance levels could be the reason for this effect. Another inverter switched off after operation at high power output for a while. Apparently, some inverters are been optimized to show excellent EU and CEC efficiency ratings. Two of the inverters featuring two inputs did not show an exceptional performance at the EU- and CEC-ratings, but they achieved top ranks at the AC energy yield for the first years. For the customer, the AC yield is a major performance indicator of any microinverter and should be included in the datasheet.
Keywords: yield; AC; micro-inverter; MPPT; CEC rating; EU efficiency; Photovoltaic; Solar

Eignung der Netzfrequenz als Instrument der Entscheidungsfindung zur Auslösung von Lastverschiebungen bei niedrigen spezifischen CO2-Emissionen und EEX-Handelspreisen - Krauter, Stefan; Zhang, L. (Tagungsband des 35. Symposiums für Photovoltaische Solarenergie, Kloster Banz, Bad Staffelstein (Deutschland))

Probability of Correct Decision–Making at Triggering of Load-Shifting Intended for low CO2-intensity and low EEX trading-prices via simple Grid Frequency Monitoring - Krauter, Stefan; Zhang, L. (Proceedings of the 14th International Renewable Energy Storage Conference, Düsseldorf (Deutschland), 10.–12. März 2020 (verschoben: 16.–18. März 2021))

European Investment in Greece in the Nineteenth Century - Schönhärl, Korinna

The Debate on student evaluations of teaching: global convergence confronts higher education traditions - Pineda, Pedro; Steinhardt, Isabel (Teaching in Higher Education)
Through co-occurrence analysis of 1139 documents (1964-2018) we identified trends in the discussions about the implementation of student teaching evaluation (SET). We found that: (1) Attention to SET originated in the US in the 1970s, spreading to German-speaking countries in the mid-1990s and continuing in China and Latin America in the early 2000s. (2) SET is commonly viewed as a control tool deserving methodological improvement, while bias is debated in the US. We also found local trajectories: (3) Whereas in the US and Latin America SET is primarily seen as a management tool, German-speaking and Chinese authors reflect more on improving teaching. Chinese scholars consider SET a valid instrument for state control associated with artificial intelligence. Also, (4) SET is commonly used in medical education in the US and the German-speaking region and in physical education in China. We conclude that SET is discussed cross-nationally but affected by national path dependencies.
Keywords: academic discourse; bibliometric review; quality assurance; student evaluation of teaching; teaching evaluation

Die Einstellung angehender Lehrkräfte zu Forschendem Lernen im Praxissemester und Referendariat - Homt, Martina; Bloh, Bea; Grosser, Christine (Forschendes Lernen in der Lehrer/innenbildung. Implikationen für Wissenschaft und Praxis)

Professionelle Lerngemeinschaften als Entwicklungsinstrument - Eine kritische Reflexion - Bloh, Thiemo; Bloh, Bea (Professionelle Lerngemeinschaften als Entwicklungsinstrument im Bildungswesen)

Theoriebasierte Fallreflexion (TFR) im Praxissemester. Didaktische Umsetzung und Evaluation. - Bonanati, Sabrina; Westphal, Petra; Wiethoff, Christoph (HLZ - Herausforderungen Lehrer*innenbildung)
Der systematischen Reflexion von Praxiserfahrungen anhand von Theorie wird in der Lehrerinnenbildung ein besonders hoher Stellenwert zugeschrieben. Auf Makroebene wurde durch die Einführung des Praxissemesters in NRW auf der einen Seite ein wichtiger Schritt zur stärkeren Verknüpfung von Schulpraxis und universitärer Ausbildung getan. Auf der anderen Seite bestehen auf der Mirkoebene immer noch Herausforderungen in der Relationierung von Theorie und Praxis für Lehramtsstudierende. Hier heißt es für Dozierende, die Lehramtsstudierende während dieses Langzeitpraktikums in universitären Veranstaltungen begleiten, tragfähige Seminarkonzepte zu entwickeln. Der vorliegende Beitrag stellt eine Methode, die Theoriebasierte Fallreflexion (TFR), mit zwei Umsetzungsvarianten vor. Damit wird eine konkrete Möglichkeit dargelegt, wie in Begleitveranstaltungen zum Praxissemester zum einen eine systematische theoretische Analyse und zum anderen die Generierung individueller Handlungsmöglichkeiten für die konkrete Schulpraxis angeleitet werden kann. Des Weiteren werden insgesamt 410 verschiedene Rückmeldungen zur Methode von insgesamt N = 93 Studierenden, welche die TFR im Rahmen einer halbtägigen Blockveranstaltung durchführten, mittels der qualitativen Inhaltsanalyse nach Mayring (2015) kategorisiert. Die Studierenden betonten in ihren Rückmeldungen besonders das Potential der TFR im Hinblick auf ein tieferes Verständnis von theoretischen Inhalten sowie hinsichtlich der Möglichkeiten zum intensiven Austausch mit Kommilitonen*innen sowie zur individuellen Reflexion schulpraktischer Situationen.
Keywords: TFR; Theoriebasierte Fallreflexion; Praxissemester; Begleitseminar; Theorie-Praxis-Verzahnung

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Demystifying TasNet: A Dissecting Approach - Heitkaemper, Jens; Jakobeit, Darius; Boeddeker, Christoph; Drude, Lukas; Haeb-Umbach, Reinhold (ICASSP 2020 Virtual Barcelona Spain)
In recent years time domain speech separation has excelled over frequency domain separation in single channel scenarios and noise-free environments. In this paper we dissect the gains of the time-domain audio separation network (TasNet) approach by gradually replacing components of an utterance-level permutation invariant training (u-PIT) based separation system in the frequency domain until the TasNet system is reached, thus blending components of frequency domain approaches with those of time domain approaches. Some of the intermediate variants achieve comparable signal-to-distortion ratio (SDR) gains to TasNet, but retain the advantage of frequency domain processing: compatibility with classic signal processing tools such as frequency-domain beamforming and the human interpretability of the masks. Furthermore, we show that the scale invariant signal-to-distortion ratio (si-SDR) criterion used as loss function in TasNet is related to a logarithmic mean square error criterion and that it is this criterion which contributes most reliable to the performance advantage of TasNet. Finally, we critically assess which gains in a noise-free single channel environment generalize to more realistic reverberant conditions.
Keywords: voice activity detection; speech activity detection; neural network; statistical speech processing

CHiME-6 Challenge:Tackling Multispeaker Speech Recognition for Unsegmented Recordings - Watanabe, Shinji; Mandel, Michael; Barker, Jon; Vincent, Emmanuel; Arora, Ashish; Chang, Xuankai; Khudanpur, Sanjeev; Manohar, Vimal; Povey, Daniel; Raj, Desh; Snyder, David; Subramanian, Aswin Shanmugam; et al. (arXiv:2004.09249)
Following the success of the 1st, 2nd, 3rd, 4th and 5th CHiME challenges we organize the 6th CHiME Speech Separation and Recognition Challenge (CHiME-6). The new challenge revisits the previous CHiME-5 challenge and further considers the problem of distant multi-microphone conversational speech diarization and recognition in everyday home environments. Speech material is the same as the previous CHiME-5 recordings except for accurate array synchronization. The material was elicited using a dinner party scenario with efforts taken to capture data that is representative of natural conversational speech. This paper provides a baseline description of the CHiME-6 challenge for both segmented multispeaker speech recognition (Track 1) and unsegmented multispeaker speech recognition (Track 2). Of note, Track 2 is the first challenge activity in the community to tackle an unsegmented multispeaker speech recognition scenario with a complete set of reproducible open source baselines providing speech enhancement, speaker diarization, and speech recognition modules.

Book review: Fictional Dialogue as Poiesis: Elizabeth Alsop’s Making Conversation in Modernist Fiction. - Mildorf, Jarmila (Diegesis)

Functions of Fictional Dialogue: Narratological and Historical Perspectives - Mildorf, Jarmila (La contribution du discours à la charactérisation des personnages biblique)

Music and Politics in the BBC Radio Adaptation of Alan Bennett’s The Madness of George III - Mildorf, Jarmila (Radio Art and Music: Culture, Aesthetics, Politics)

Radio Art and Music: An Introduction - Mildorf, Jarmila; Verhulst, Pim (Radio Art and Music: Culture, Aesthetics, Politics)

Book Review: Storytelling as Narrative Practice: Ethnographic Approaches to the Tales We Tell, Elizabeth A. Falconi, Kathryn E. Graber (Eds.), Brill, Leiden (2019) - Mildorf, Jarmila (Journal of Pragmatics)

Erzähllogik und Krankheitserfahrung: Siri Hustvedts The Shaking Woman - Mildorf, Jarmila (Jahrbuch Literatur und Medizin, vol.12)

„Wie tief der kern dieses Volkes dem antiken wesen verwandt ist“ „Cultural Brokers“ und ihre Strategien zur Vermittlung des Unbekannten - Schönhärl, Korinna (Historische Zeitschrift)
Der vorliegende Aufsatz fragt nach Strategien kultureller Vermittler, den bei der Erstbegegnung mit einer fremden Kultur eintretenden Schock zu verarbeiten und die kulturellen Differenzen neu zu semantisieren und sinnhaft zu deuten. Er greift drei geografisch und chronologisch weit auseinanderliegende Fallbeispiele von kulturellen Vermittlern auf, die vor dem Hintergrund ihres umfassenden antiken Bildungswissens versuchten, die Fremde als „lebende Antike“ zu interpretieren: Missionare in Neuspanien im 16. und 17. Jahrhundert, einen Griechenlandreisenden der 1830er und einen Japanreisenden der 1930er Jahre. Der analysierte Vermittlungsprozess wird als „doppelte Allelopoiese“ beschrieben: die brokers stilisierten einerseits die Antike als zwar weit zurückliegenden, aber essentiellen Teil ihrer eigenen kulturellen Identität; sie parallelisierten andererseits die fremde Lebenswelt, mit der sie konfrontiert wurden, mit eben dieser Antike; in einem (nur analytisch zu isolierenden) dritten Schritt konnten sie so Parallelen zwischen der Fremde und dem Eigenen hervorheben und wechselseitige kulturelle Aneignungen (Transformationen) einleiten und rechtfertigen. Der Artikel schlägt eine weitere Ausarbeitung der „doppelten Allelopoiese“ als analytisches Instrument für die Erforschung der cultural brokers vor.
Keywords: History

Das griechische Referendum von 2015 über die Konditionen der Euro-Gruppe - Schönhärl, Korinna (Südosteuropa Mitteilungen)

Radio Art and Music: Culture, Aesthetics, Politics

Ambivalenzen der Förderung: Erziehungs- und Lernbegleitung für Kinder, Jugendliche und junge Erwachsene durch studentische Mentorinnen und Mentoren - Beerheide, N.; Dopheide, F.; Freitag, C.; Koch, L.; Struchholz, C.; Westphal, Petra (ESE Emotionale und soziale Entwicklung in der Pädagogik der Erziehungshilfe und bei Verhaltensstörungen)

Herausforderungen studentischen Peer-Mentorings. Eine Situationsanalyse vor dem Hintergrund universitärer Arenen - Westphal, Petra

Variational integrators for dissipative systems - Limebeer, D. J. N.; Ober-Blöbaum, Sina; Farshi, F. H. (IEEE Transactions on Automatic Control)

Explicit Multi-objective Model Predictive Control for Nonlinear Systems Under Uncertainty - Hernández Castellanos, Carlos Ignacio; Ober-Blöbaum, Sina; Peitz, Sebastian (International Journal of Robust and Nonlinear Control)
In real-world problems, uncertainties (e.g., errors in the measurement, precision errors) often lead to poor performance of numerical algorithms when not explicitly taken into account. This is also the case for control problems, where optimal solutions can degrade in quality or even become infeasible. Thus, there is the need to design methods that can handle uncertainty. In this work, we consider nonlinear multi-objective optimal control problems with uncertainty on the initial conditions, and in particular their incorporation into a feedback loop via model predictive control (MPC). In multi-objective optimal control, an optimal compromise between multiple conflicting criteria has to be found. For such problems, not much has been reported in terms of uncertainties. To address this problem class, we design an offline/online framework to compute an approximation of efficient control strategies. This approach is closely related to explicit MPC for nonlinear systems, where the potentially expensive optimization problem is solved in an offline phase in order to enable fast solutions in the online phase. In order to reduce the numerical cost of the offline phase, we exploit symmetries in the control problems. Furthermore, in order to ensure optimality of the solutions, we include an additional online optimization step, which is considerably cheaper than the original multi-objective optimization problem. We test our framework on a car maneuvering problem where safety and speed are the objectives. The multi-objective framework allows for online adaptations of the desired objective. Alternatively, an automatic scalarizing procedure yields very efficient feedback controls. Our results show that the method is capable of designing driving strategies that deal better with uncertainties in the initial conditions, which translates into potentially safer and faster driving strategies.

Numerical computation of lightly multi-objective robust optimal solutions by means of generalized cell mapping - Hernández Castellanos, C. I. O.; Schütze, G.; Sun, J.-Q.; Ober-Blöbaum, Sina; Morales-Luna, G. (Mathematics)

A multirate variational approach to simulation and optimal control for flexible spacecraft - Lishkova, Y.; Ober-Blöbaum, Sina; Cannon, M.; Leyendecker, S. (Accepted for publication in Proceedings of 2020 AAS/AIAA Astrodynamics Specialist Conference - Lake Tahoe)

A dissipativity characterization of velocity turnpikes in optimal control problems for mechanical systems - Faulwasser, T.; Flaßkamp, K.; Ober-Blöbaum, Sina; Worthmann, K. (24th International Symposium on Mathematical Theory of Networks and Systems)

Modelling of the convection-diffusion equation through fractional restricted calculus of variations - Cresson, J.; Jiménez, F.; Ober-Blöbaum, Sina (24th International Symposium on Mathematical Theory of Networks and Systems)

Optimizing spontaneous parametric down-conversion sources for boson sampling - van der Meer, R.; Renema, J. J.; Brecht, Benjamin; Silberhorn, Christine; Pinkse, P. W. H. (Physical Review A)

On Weyl’s type theorems and genericity of projective rigidity in sub-Riemannian geometry - Jean, Frédéric; Maslovskaya, Sofya; Zelenko, Igor (Geometriae Dedicata)
Keywords: Geometry and Topology

The turnpike property in maximization of microbial metabolite production - Maslovskaya, Sofya; Caillau, Jean-Baptiste; Djema, Walid; Giraldi, Laetitia; Jean-Luc, Jean-Luc; Pomet, Jean-Baptiste

Zermelo-Markov-Dubins problem and extensions in marine navigation - Caillau, Jean-Baptiste; Maslovskaya, Sofya; Mensch, Thomas; Moulinier, Timothee; Pomet, Jean-Baptiste (2019 IEEE 58th Conference on Decision and Control (CDC))

Die Kosten der Rettung Europas: Schulden- und Steuerkulturen in historischer Perspektive - Schönhärl, Korinna; Buggeln, Marc

INRISCO: INcident monitoRing in Smart COmmunities - Aguilar'Igartua, Mónica; Almenárez-Mendoza, Florina; P. Díaz Redondo, Rebeca; I. Martín'Vicente, Manuela; Forné, Jordi; Campo, Celeste; Fernández Vilas, Ana; J. de la Cruz Llopis, Luis; García-Rubio, Carlos; Marín-López, Andrés; Mohamad Mezher, Ahmad; Díaz Sánchez, Daniel; et al. (IEEE Access)

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarbøe, Odvar M. (Journal of Economic Behavior & Organization)
Many countries have opened their health care markets to private for-profit providers, aiming to promote quality and choice for patients. The prices are regulated and providers compete in location and quality. We show that whereas opening a public hospital market typically raises quality, the private provider strategically locates towards the corner of the market to avoid costly quality competition. Social welfare depends on the size of the regulator's budget and on the altruism of the public provider. If the budget is large, high quality results and welfare is highest in a duopoly whenever entry is optimal. If the budget is small, quality levels in a duopoly mirror the quality level in a monopoly. It can be optimal for the regulator not to use the full budget.

Review: Günther Schulz, Mark Spoerer (Ed.): Integration und Desintegration Europas: Wirtschafts- und sozialhistorische Beiträge (VSWG Beiheft 244), Stuttgart 2019 - Schönhärl, Korinna (Journal of European Integration History)

Integrated model-driven development of self-adaptive user interfaces - Yigitbas, Enes; Jovanovikj, Ivan; Biermeier, Kai; Sauer, Stefan; Engels, Gregor (Software and Systems Modeling)
Modern user interfaces (UIs) are increasingly expected to be plastic, in the sense that they retain a constant level of usability, even when subjected to context changes at runtime. Self-adaptive user interfaces (SAUIs) have been promoted as a solution for context variability due to their ability to automatically adapt to the context-of-use at runtime. The development of SAUIs is a challenging and complex task as additional aspects like context management and UI adaptation have to be covered. In classical model-driven UI development approaches, these aspects are not fully integrated and hence introduce additional complexity as they represent crosscutting concerns. In this paper, we present an integrated model-driven development approach where a classical model-driven development of UIs is coupled with a model-driven development of context-of-use and UI adaptation rules. We base our approach on the core UI modeling language IFML and introduce new modeling languages for context-of-use (ContextML) and UI adaptation rules (AdaptML). The generated UI code, based on the IFML model, is coupled with the context and adaptation services, generated from the ContextML and AdaptMLmodel, respectively. The integration of the generated artifacts, namely UI code, context, and adaptation services in an overall rule-based execution environment, enables runtime UI adaptation. The benefit of our approach is demonstrated by two case studies, showing the development of SAUIs for different application scenarios and a usability study which has been conducted to analyze end-user satisfaction of SAUIs.
Keywords: Modelling and Simulation; Software

Digitalisierung in der Landwirtschaft. Gründe, Optionen und Bewertungen aus Perspektive von Milchviehlandwirtinnen und -landwirten - Goller, Michael; Caruso, Carina; Berisha-Gawlowski, Angelina; Harteis, Christian (Digitalisierung am Übergang Schule Beruf Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Berufliche Förderung in Zeiten von Digitalisierung und Berufsbildung 4.0 war ein Schwerpunktthema der Hochschultage Berufliche Bildung 2019 in Siegen. Die Beiträge des Sammelbandes geben einen Überblick über die diskutierten Konzepte und Handlungsansätze. Der erste Teil befasst sich mit Fragen zum digitalen Kompetenzerwerb in verschiedenen Arbeitsdomänen, von den Auswirkungen der Digitalisierung auf industrieller Arbeit und Landwirtschaft bis zur Entwicklung von Medienkompetenz als Aufgabe der Berufsbildung. Im zweiten Teil stehen Fragen zur beruflichen Förderung in Zeiten der Digitalisierung im Mittelpunkt. Themen sind u.a. Lernortkooperationen, digitale Transformation in der Ausbildungsvorbereitung an Berufskollegs sowie Benachteiligtenförderung in digitalen Kontexten. Der Band richtet sich an Wissenschaftler und Wissenschaftlerinnen sowie Akteure und Akteurinnen in der beruflichen Bildung, im Übergangssystem, in der beruflichen Förderung und an Berufsschulen.
Keywords: Arbeitsmarktförderung; Arbeitswelt; Arbeitswelt - Strukturwandel; Benachteiligte; Beruf; Berufliche; Bildungberufliches Lernen; Berufskolleg; Berufswahl; Didaktik; Digitale Arbeitswelt; Digitale Bildung; Digitale Kompetenzen; Digitale Lehre; Digitales Lernen; Digitalisierung; Industrie 4.0; Landwirtschaft; Lernprozess; Lernprozesse; Lernprozesse und -begleitung; Medienkompetenz; Übergangsmanagement

The contribution of mental simulation to the development of intuition - Steffen, Bianca; Goller, Michael; Harteis, Christian (Intuition handbook: Bridging research and practice)
How can intuition research inform practice? As the use of intuition in business has become more widely accepted, companies struggle to understand how to use this additional resource efficiently, while corporate trainers and university educators lack tools to develop it as a skill. This truly international Handbook provides relevant answers with: • chapters by academics and practitioners, written in a concise, digestible format to make it accessible to non-academic readers • empirical studies from multiple industry/service sectors that demonstrate an integrated use of intuition and analysis in decision making • studies from industry and education that demonstrate how to develop intuition, including a ground-breaking research in problem solving • non-Western perspectives illustrated on case studies from Japan and China • use of language protocols/methods to bring intuition into our awareness • new research into group/collective intuition (based on language analysis and quantum physics) • research related to sensing and sense making. Due to its focus on bridging theory and practice, the Handbook is of value not only to academics and organizational researchers but also to industry professionals, corporate trainers and university educators who search for answers on how to incorporate intuition into a common skill set. Accessible in style, it will also appeal to educated business readers.

Schulstationen in der Pflegeausbildung: Zur Lernförderlichkeit eines komplexen Lehr-Lernarrangements - Goller, Michael; Steffen, Bianca; Lau, Dirk (Zeitschrift für Berufs- und Wirtschaftspädagogik)
In der beruflichen Pflegeausbildung bezeichnen Schulstationen spezielle Lehr-Lernarrangements, in welchen Auszubildende zeitlich beschränkt die volle Verantwortung für die Planung, Organisation und Umsetzung der Patient*innenpflege auf einer Station im regulären Krankenhausbetrieb übernehmen. Obwohl solche Schulstationen seit mehr als 20 Jahren in der Ausbildung eingesetzt werden und ihnen in der Literatur im Vergleich zu den regulären Praxisphasen lernförderliche Eigenschaften zugeschrieben werden, so fehlen bisher empirische Studien, welche die unterstellten Lernpotentiale überprüfen. Der vorliegende Beitrag nimmt sich dieser Forschungslücke an. Vor diesem Hintergrund soll die folgende erkenntnisleitende Forschungsfrage beantwortet werden: Wie unterscheiden sich Schulstationen von regulären Praxisphasen in Hinblick auf lernförderliche Arbeitsplatzmerkmale? Hierzu wurde eine Mixed-Methods-Replikationsstudie durchgeführt, in welcher zwei konsekutiv stattfindende Schulstationen mittels schriftlicher Befragung (insgesamt 36 Auszubildende) sowie anschließender Interviews mit insgesamt 25 Auszubildenden, drei examinierten Pflegefachkräften und drei involvierten Ärzt*innen untersucht wurden. Als zentrales Ergebnis dieser Studie kann festgehalten werden, dass die untersuchte Schulstation im Vergleich zu den regulären Praxisphasen der Auszubildenden für arbeitsplatzgebundene Lernprozesse tatsächlich förderlicher gestaltet ist. Auf Basis der empirischen Befunde werden Bedingungen abgeleitet, die für die Realisation der identifizierten Lernpotentiale erfüllt sein sollten.
Keywords: Pflegeausbildung; Schulstation; Lernen am Arbeitsplatz; Arbeitsplatzgebundenes Lernen; Informelles Lernen

Engineering students' learning during internships: Exploring the explanatory power of the job demands‐control‐support model - Goller, Michael; Harteis, Christian; Gijbels, David; Donche, Vincent (Journal of Engineering Education)

Lernen zu Unterrichten – Veränderungen in den Einstellungsmustern von Lehramtsstudierenden während des Praxissemesters im Zusammenhang mit mentorieller Lernbegleitung und Kompetenzeinschätzung - Gröschner, Alexander; Goller, Michael; Haschner, Tina (Praxissemester im Lehramtsstudium in Deutschland: Wirkungen auf Studierende)
Lehramtsstudierende unterscheiden sich in ihren Einstellungen, wie das Lernen zu Unterrichten am besten gelingt und welche Lernaktivitäten und Formen der Emotionsregulation dazu nötig sind. In der Studie wurden die Einstellungsmuster von N = 512 Studierenden (2. Mastersemester) zu Beginn und gegen Ende des Langzeitpraktikums Praxissemester mittels dem Inventory Learning to Teach Process (ILTP) erhoben und mögliche Zusammenhänge mit der Lernbegleitung durch Mentor/innen sowie mit der individuellen Kompetenzeinschätzung geprüft. Entgegen der theoretisch angenommen Muster wurden drei Muster (Vermeidend, Praxisorientiert, Vielseitig) identifiziert. Die Studie zeigt, dass eine hochwertig eingeschätzte mentorielle Begleitung mit dem Beibehalt oder dem Wechsel in das Muster Vielseitig in Relation steht und dass Kompetenzeinschätzungen Zusammenhänge mit den Einschätzungsmustern aufweisen. So empfinden diejenigen Studierenden den höchsten Kompetenzzuwachs, die während des Praxissemesters in das Muster Vielseitig wechseln bzw. in diesem verbleiben. Den geringsten Kompetenzzuwachs verzeichnen die Studierenden, die nach dem Praxissemester dem Muster Vermeidend zugeordnet wurden. Implikationen für die weitere Forschung zur Bedeutsamkeit im Umgang mit heterogenen Lerngruppen werden diskutiert.
Keywords: Kompetenzeinschätzung; Lehramtsstudium; Lernen zu Unterrichten; Mentoring; Praxissemester

Conceptual Change in the Face of Digitalization: Challenges for Workplaces and Workplace Learning - Harteis, Christian; Goller, Michael; Caruso, Carina (Frontiers in Education)

Auswirkungen der Digitalisierung industrieller Arbeit auf die berufliche und allgemeine Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung am Übergang Schule Beruf: Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Keywords: Arbeitsmarktförderung; Arbeitswelt; Arbeitswelt - Strukturwandel; Benachteiligte

Keine Klimaneutralität ohne Energieeffizienz – Wie Datenbanken helfen können, Energieeffizienzpotenziale zu heben - Ebersold, Felix; Reineke, Patrick; Meschede, Henning; Hesselbach, Jens (BWK Das Energie Fachmagazin)

Energy efficiency in industrial processes – best practice - Meschede, Henning

A New Approach for the Evaluation of Component and Joint Loads Based on Load Path Analysis - Steinfelder, C.; Brosius, A. (Lecture Notes in Production Engineering)

wirmüssentanzen. Methodische Überlegungen zur linguistischen Analyse von (Selbst-) Inszenierungen von Amateursportlern in den sozialen Medien am Beispiel Racing Aloha auf Instagram - Kurpiers, Anna-Katharina (Kommunikationsdynamiken zwischen Mündlichkeit und Schriftlichkeit. Festschrift für Barbara Job zum 60. Geburtstag)

Analyzing Political Bias and Unfairness in News Articles at Different Levels of Granularity - Chen, Wei-Fan; Al-Khatib, Khalid; Wachsmuth, Henning; Stein, Benno (Proceedings of the Fourth Workshop on Natural Language Processing and Computational Social Science)

Task Proposal: Abstractive Snippet Generation for Web Pages - Syed, Shahbaz; Chen, Wei-Fan; Hagen, Matthias; Stein, Benno; Wachsmuth, Henning; Potthast, Martin (Proceedings of the 13th International Conference on Natural Language Generation (INLG 2020))

Detecting Media Bias in News Articles using Gaussian Bias Distributions - Chen, Wei-Fan; Al-Khatib, Khalid; Stein, Benno; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: EMNLP 2020)

Abstractive Snippet Generation - Chen, Wei-Fan; Syed, Shahbaz; Stein, Benno; Hagen, Matthias; Potthast, Martin (Proceedings of the Web Conference 2020)

Target Inference in Argument Conclusion Generation - Alshomary, Milad; Syed, Shahbaz; Potthast, Martin; Wachsmuth, Henning (Proceedings of 58th Annual Meeting of the Association for Computational Linguistics (ACL 2020))

Dynamic Multi-Frequency Test Method for Hidden Interconnect Defects - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille (38th IEEE VLSI Test Symposium (VTS))

Logic Fault Diagnosis of Hidden Delay Defects - Holst, Stefan; Kampmann, Matthias; Sprenger, Alexander; Reimer, Jan Dennis; Hellebrand, Sybille; Wunderlich, Hans-Joachim; Weng, Xiaoqing (IEEE International Test Conference (ITC'20), November 2020)

„So dacht ich. Demnächst mehr.“ Modelle narrativer Ethik und narrativer Identität in Hölderlins ‚Hyperion’ und Schillers ‚Demetrius’ - van Laak, Lothar (Erzähltes Selbst. Narrative Ethik aus theologischer und literaturwissenschaftlicher Sicht. (Theologie - Kultur - Hermeneutik, Bd. 27))

Barock im Norden. Kommunikationspraxis und Kulturtransfer - van Laak, Lothar; Ehland, Christoph; Münzmay, Andreas; Schmitz, Sabine; Süßmann, Johannes (Peter Paul Rubens und der Barock im Norden. Katalog zur Ausstellung im Erzbischöflichen Diözesanmuseum Paderborn)

„eine andere Ähnlichkeit“ – Musik und Literatur bei Moses Mendelssohn und Gotthold Ephraim Lessing - van Laak, Lothar (Dialog der Künste. Literatur und Musik)

Erzählen und Ehtik in Peter Weiss’ ‚Rekonvaleszenz’. In: Erzähltes Selbst. Narrative Ethik aus theologischer und literaturwissenschaftlicher Sicht - van Laak, Lothar ((Theologie - Kultur - Hermeneutik, Bd. 27).)

„Wer kann durchs Fernrohr der Metaphern sehen?“ Beobachtungen an Durs Grünbeins Mond-Zyklus ‚Cyrano oder Die Rückkehr vom Mond‘ - van Laak, Lothar (Museum als Resonanzraum)